Role of Self-Esteem People Living with HIV (PLHIV) in HIV Prevention Behavior: A Literature Review - Kristiani Kristiani; Syamsul Arifin; Adi Nugroho; Ermina Istiqomah; Husaini Husaini; Lenie Marlinae; Rusdi Rusli (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) remain significant public health challenges worldwide, impacting both clinical outcomes and psychosocial well-being. People living with HIV (PLHIV) often face stigma and discrimination, which can lower self-esteem. Reduced self-esteem is linked to increased engagement in risky behaviors that may facilitate HIV transmission. This study investigates how self-esteem influences HIV prevention behaviors among PLHIV. Methods: A scoping review was conducted using the Population, Exposure, Outcome, Study Design (PEOS) framework. The literature search covered PubMed, ScienceDirect, EBSCO, and Google Scholar. Eligible articles were English-language primary studies published from 2020 to 2024. The search used the keywords: “HIV Infections” AND “PLHIV” AND “self-esteem” OR “self-concept.” The selection process followed PRISMA guidelines. Results: Fifteen articles were analyzed. Findings indicate that self-esteem significantly influences HIV prevention behaviors, including status disclosure, antiretroviral therapy adherence, safe sex practices, and viral suppression. Self-esteem also acts as a mediator and protective factor against stigma and mental health disorders. Conclusion: Self-esteem is a key psychosocial factor in preventing HIV transmission among PLHIV. Incorporating self-esteem interventions into HIV programs may improve prevention outcomes and quality of life.